Chapter Il faculty developer per la formazione del docente universitario. Questioni aperte e prospettive di didattica avanzata - Perla, Loredana (Studies on Adult Learning and Education, 2022)
The recent Recommendations of the Ministers of the European Higher Education Area (BFUG, 2020) have highlighted how the qualification processes of university teaching are closely related to didactic approaches student's-centered. To facilitate change actions, institutions identify mediation figures within the university with the function of managing Faculty Development actions and programs. The chapter outlines the role of the faculty developer and considers him an educational "agent of change". Faculty developers can create a network for the professional and organizational development of a university, favoring the construction of communities of practice and multi-transdisciplinary connections.